Recent Advances for Wastewater Treatment on Polyvinylidene Fluoride-Based Membrane: A Review - Mohamat, Rosmanisah; Abu Bakar, Suriani; Mohamed, Azmi; Muqoyyanah, Muqoyyanah; Othman, Mohd Hafiz Dzarfan; Rohani, Rosiah; Mamat, Mohamad Hafiz; Ahmad, Mohd Khairul; Malek, Mohd Firdaus; Khalil, H. P. S. Abdul; Ali, Khuram (International Journal of Integrated Engineering, 2024)
The development of scalable membrane-based separation processes has attracted considerable interest on laboratory and industrial scales. Polyvinylidene fluoride (PVDF) is one of the most widely used fluoropolymer materials for membrane fabrication due to its excellent mechanical strength, good thermal stability and chemical resistance as well as aging resistance. However, the hydrophobic nature of PVDF has resulted in serious membrane fouling during the filtration process. From the past decade, the embedment of hydrophilic materials in/on PVDF-based membranes can significantly alter the membrane’s morphology and surface properties. Therefore, based on most articles retrieved from Web of Science, Scopus, Google Scholar, etc., this article provides the overview of the recent development of PVDF-based membranes during the recent several decades. The detailed information regarding PVDF as a polymer material as well as the main challenge in the development of PVDF-based membranes with better performance was summarised. Moreover, the factors influencing membrane fouling including surface hydrophilicity, roughness and charge are also addressed. Then, the PVDF-based membrane preparation and its recent modification via the blending method were discussed. Finally, the overview and future perspective of PVDF-based membrane development are reviewed. Overall, it can be concluded that PVDF-based membranes have great potential for further advances towards the development of membrane technologies for the future.